2015
DOI: 10.1016/j.ijcard.2015.05.185
|View full text |Cite
|
Sign up to set email alerts
|

Blood-based microRNA signatures differentiate various forms of cardiac hypertrophy

Abstract: Background Hypertrophic cardiomyopathy (HCM) is caused by mutations in different structural genes and induces pathological hypertrophy with sudden cardiac death as a possible consequence. HCM can be separated into hypertrophic non-obstructive and obstructive cardiomyopathy (HNCM/HOCM) with different clinical treatment approaches. We here distinguished between HNCM, HOCM, cardiac amyloidosis and aortic stenosis by using microRNA profiling and investigated potential interactions between circulating miRNA levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 21 publications
3
79
1
Order By: Relevance
“…The increase in Hcn2 mRNA atrial expression at baseline was expected (Fig. 2D) because we have previously observed that TRβ Δ337T mice exhibit significant increases in heart rate [52] under baseline conditions compared with TRβ WT animals with a cardiac phenotype very similar to hyperthyroidism. This increased HR occurs because the TRβ Δ337T animals have high serum concentrations of TH, which interact with THRα1.…”
Section: Cell Physiolsupporting
confidence: 67%
“…The increase in Hcn2 mRNA atrial expression at baseline was expected (Fig. 2D) because we have previously observed that TRβ Δ337T mice exhibit significant increases in heart rate [52] under baseline conditions compared with TRβ WT animals with a cardiac phenotype very similar to hyperthyroidism. This increased HR occurs because the TRβ Δ337T animals have high serum concentrations of TH, which interact with THRα1.…”
Section: Cell Physiolsupporting
confidence: 67%
“…PLSR analysis gave quantitative outputs to how likely each microRNA was involved in our response. Certain microRNA’s identified by our anaylsis have been shown to regulate important function like fibrosis (miR-27a and miR-29c 26, 27 ), cardiac hypertrophy (miR-29c 28 , miR-96 29, 30 , miR-182 31, 32 and miR-185 33 ), angiogenesis (miR-27a 34 ), and apoptotsis (miR-138 35, 36 , miR-25 37 ). Although, our model is predictive of microRNA-based mechanism, these targets still need to be validated in the future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Several miRNAs have recently been linked to the diagnosis of HF 34, 35. Based on our screening results as well as literature findings,36, 37 several ‘cardiac remodelling’‐associated miRNAs and lncRNAs have been chosen to be tested in the FIBROTARGETS patient populations to determine their use for improving diagnosis of HF, risk and patient stratification, and prediction of individual patient prognosis. Standardized miRNA‐ or lncRNA‐specific PCR‐based protocols and normalization procedures are currently being used to achieve this goal.…”
Section: Non‐coding Rnasmentioning
confidence: 99%